Wreck-it Ralph Book of the film - Disney Enterprises, Inc (london Parragon Books, 2012)
Tired of always being the one who destroys things, Ralph leaves his game and embarks on a quest to win a medal in another game and prove his worth as a hero. His journey leads him to various game worlds, including a first-person shooter and a candy-themed racing game called "Sugar Rush", where he inadvertently unleashes a deadly enemy that threatens the entire arcade. Ultimately, Ralph must team up with a glitchy racer named Vanellope von Schweetz to save the arcade and find his own path to heroism.